Improving Mathematical Understanding Through the Use of Wordwall Media in Elementary Schools - Emilia, Firda; Rulyansah, Afib; Amin, Siti Maghrirotun; Nafiah, Nafiah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to investigate the effectiveness of using WordWall media in improving the understanding of mathematical concepts at the elementary school level. The research method involves a literature review that includes a critical evaluation of literature related to mathematical concepts and WordWall media. Data analysis was conducted thematically with a qualitative synthesis approach, resulting in four main themes and twelve sub-themes. The study's findings indicate a positive impact of using WordWall on students' understanding of mathematical concepts. The average learning outcome scores increased significantly, and there was an improvement in students' mastery of learning through WordWall Gameshow. This medium also proved effective in enhancing students' learning motivation, creating an interactive learning environment, and boosting active participation and collaborative skills among students. WordWall was found to be more effective compared to some other learning media, contributing positively to learning outcomes and student motivation. WordWall also helps overcome students' difficulties in understanding mathematical concepts by providing visual representations and vocabulary support. Thus, WordWall is considered an effective learning tool for improving the understanding of mathematical concepts among elementary school students. The study's conclusion confirms that WordWall successfully achieved its objectives with high significance. However, the study has limitations such as sample size and relatively short research duration. Recommendations for future research include conducting comparative studies with other mathematical learning media, examining the influence of the social environment, developing more specific WordWall learning models, and exploring long-term effects and the correlation between student learning motivation and mathematical learning outcomes. Research on the effectiveness of WordWall in virtual mathematics learning environments is also an interesting area for further study.